Identification of the Quality of the Covid-19 Monument Public Open Space - Ahmad Alamudin; Inne Yuwinarsih (Jurnal Arsitektur Archicentre, 2024)
The Bandung City Government has temporarily closed the city park since the COVID-19 outbreak began. The community is looking for an alternative public open space because the city park is closed. The COVID-19 Monument Park in Bandung will be the main subject of study. The subject of this study occupies a space in an active environmental park. To study what elements influence the success of Covid-19 parks as empty spaces in urban settlements, this study intends to investigate the quality of public open spaces in more detail, especially Covid-19 parks in terms of physical aspects and their utilization activities. Based on these findings, a qualitative approach and descriptive analysis were used in this research technique.